Awareness Deficits in Children and Adolescents After Traumatic Brain Injury. Issue 5 (September 2015) - Lloyd, Owen; Ownsworth, Tamara; Fleming, Jennifer; Zimmer-Gembeck, Melanie J.; Caplan, Bruce; Bogner, Jennifer; Brenner, Lisa
<x xml:space="preserve">Abstract</x> Objectives: To systematically review empirical research on awareness deficits in children and adolescents following traumatic brain injury (TBI). Methods: PsycINFO, MEDLINE, Cochrane Library, CINAHL (Cumulative Index to Nursing and Allied Health Literature), ERIC (Education Resources Information Centre), PsycBITE, and Web of Science were searched from inception to August 8, 2013, using key terms relating to awareness of deficits and brain injury in childhood/adolescence. Studies of children or adolescents with traumatic brain injury (TBI), systematic measurement of awareness of deficits, and reporting of quantitative data were included. Details of participants, methodology, and findings were summarized for each study, and methodological quality was rated. Results: Review of 12 eligible studies yielded mixed evidence concerning the presence of awareness deficits after childhood TBI. Awareness deficits were most evident both for memory and executive function impairments and for children and adolescents with severe TBI. Methodological variability, including sampling characteristics, objects of awareness, measurement issues, and approach to statistical analysis, contributed to the mixed findings. Conclusions: Further research focusing on factors contributing to awareness deficits following pediatric TBI, the course of recovery, and relation to functional outcomes is warranted.